The origin of rhythmic magmatic layering in coarse-grained porphyritic S-type granite of the Peninsula pluton, Cape Granite Suite, South Africa - Ramphaka, Priscilla L. (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.